An evidence-based framework for determining the optimal amount of intervention for autistic children. (December 2021) - Trembath, David; Waddington, Hannah; Sulek, Rhylee; Varcin, Kandice; Bent, Catherine; Ashburner, Jill; Eapen, Valsamma; Goodall, Emma; Hudry, Kristelle; Silove, Natalie; Whitehouse, Andrew
Summary: The provision of timely, effective, and socially valid non-pharmacological intervention is at the core of efforts to support the development of young autistic children. These efforts are intended to support children to develop skills, empower their caregivers, and lay the foundation for optimal choice, independence, and quality of life into adulthood. But what is the optimal amount of intervention? In this Viewpoint, we review current guidelines and consider evidence from an umbrella review of non-pharmacological interventions for autistic children aged up to 12 years. We show the lack of consensus on the issue, identify factors that might be relevant to consider, and present an evidence-based framework for determining the optimal amount of intervention for each child, along with recommendations for future research.